A facile route to design pH-responsive viscoelastic wormlike micelles: Smart use of hydrotropes - Lin, Yiyang; Han, Xue; Huang, Jianbin; Fu, Honglan; Yu, Cailan (Journal of colloid and interface science, 2009)
A simple and effective route to design pH-responsive viscoelastic wormlike micelles based on commercial compounds is reported. According to this route, pH-sensitive viscoelastic fluids can be easily obtained by introducing a pH-responsive hydrotrope into a surfactant solution. In this paper, the mixed system of cetyltrimethylammonium bromide (CTAB) and potassium phthalic acid (PPA) was studied in detail. This pH-sensitive fluid can be switched between a gellike state and a waterlike state within a narrow pH change. Rheology and DLS results revealed that the pH-sensitive flowing behavior was attributed to the microstructure transition between wormlike micelles and short cylindrical micelles. Combined with fluorescence anisotropy, NMR, and UV–vis, it was demonstrated that the pH response of viscoelastic fluid originated from the different binding abilities of hydrotrope to surfactant as pH varies. Furthermore, different kinds of hydrotropes can be utilized to prepare pH-responsive viscoelastic fluids in the desired pH areas. The pH-responsive viscoelastic wormlike micelle solution is characterized by a macroscopic appearance and repeated viscosity switch.